TYPES OF SYSTOLIC ARTERIAL BLOOD PRESSURE ORTHOSTATIC REACTIONS IN PATIENTS WITH ARTERIAL HYPERTENSION - Garkaviy, P.A.; Yegorova, A.Yu.; Yabluchanskіy, N.I. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
Peculiarities of systolic arterial blood pressure (SABP) changes during the clino/orthotatic test in patients with primary arterial hypertension (AH). 154 patients were investigated, (58 males and 94 females), median age 63±7 years. Average duration of AH was 10,4±7,8 years. 48 patients had mild AH, 55 had moderate AH, 51 had severe AH. According to the changes of SABP during the orthostatic test patients were divided into 3 groups: increase of SABP – group 1 (hypertonic type), no changes of SABP – group 2 (isotonic type), decrease of SABP – group 3 (hypotonic type). Minimal change on5 mmwas a criteria of SABP increase or decrease.During the transition from clinostasis to orthostasis 67,5% of patients had SABP increase, 11,7% of patients had no changes of SABP and in 20,8% of patients SABP decreased.Hypertonic type of reaction was more frequent in males (81%), than in females (59,4%). Hypotonic and isotonic types were seen less frequent in males (in 12,1% and in 6,9% of patients respectively), than in females (in 26% and in 14,6% of patients respectively).Variations in diastolic and systolic blood pressure parameters that were found during orthostatic tests indicate on the importance of conducting a separate comparative and descriptive investigation with using control group.